2012
DOI: 10.1016/s1734-1140(12)70882-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin II type 1 receptor blocker on osteoporotic rat femurs

Abstract: Blockage of AT1 receptor increased strength, mass and trabecular connections of ovariectomized rat femurs. Therefore, it is tempting to speculate that drugs, including AT1 receptor blockers, may be used for the treatment of osteoporosis or reduction of its detrimental effects in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…The study of the potential effects of Ang II and its inhibitors on bone mineral density (BMD) has been an area of intense interest and has has yielded conflicting results. While Losartan increased bone mass and strength in ovariectomized osteoporotic female rat femurs [12], it failed to improve bone mass loss in orchiectomized male rats [21]. Broulík et al found that the use of Losartan and Enalapril was not associated with increased bone mass in intact female rats [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the potential effects of Ang II and its inhibitors on bone mineral density (BMD) has been an area of intense interest and has has yielded conflicting results. While Losartan increased bone mass and strength in ovariectomized osteoporotic female rat femurs [12], it failed to improve bone mass loss in orchiectomized male rats [21]. Broulík et al found that the use of Losartan and Enalapril was not associated with increased bone mass in intact female rats [22].…”
Section: Discussionmentioning
confidence: 99%
“…Th ey also showed the expression of RAS components for the first time during fracture healing, and that ACEIs decreased fi brosis in the early phase of a fracture. Based on these findings, we have designed a study to compare the influences of ACEIs and ARBs on fracture healing and hypothesized that, owing to the substantial data that AngII exerts its effects on bone mainly via AT1 receptor [6,7,10,11,12], ARBs should be as successful as ACEIs for stimulating fracture healing.…”
mentioning
confidence: 99%
“…2) The experimental studies have showed the beneficial effects of ACEI and ARB on maintaining bone health of ovariectomized (OVX) rats 11,18,19) and mice, 10,20) an animal model mimicking postmenopausal osteoporosis due to the decline of circulating estrogen level. While, given renin is the rate-limiting enzyme of the RAS, whether the RAS inhibition by inhibiting renin activity could show beneficial effects on postmenopausal osteoporosis is not known.…”
Section: )mentioning
confidence: 99%
“…Typical force-displacement and stress-strain curves obtained from the tensile test were analyzed as described before (Donmez et al 2012). By this way ultimate tensile load, ultimate tensile strength, strain, stiffness, tensile modulus (Young's modulus) was measured.…”
Section: Calculation Of Biomechanical Datamentioning
confidence: 99%
“…Furthermore the tensile modulus (MPa) was then calculated as follows: E = Δσ/Δε where ε is the strain. The strain (% displacement) was obtained by the equation: ε = ΔL/L 0 , where ∆L is the change in the length and L 0 is the original length (Donmez et al 2012). …”
Section: Calculation Of Biomechanical Datamentioning
confidence: 99%